Development of drive cycle and emission models for in-use tricycles in Metro Manila - Abuzo, Anabel A. (2005)
Tricycles are three-wheeled motorcycles with a sidecar/couch, which are used as a public transport in the Philippines. The government legalized tricycles in 1985 and by 1991, the local government units were authorized to handle the franchise of tricycles. About 1.3 million motorcycles/tricycles (MC/TC) are presently registered, with 12.1% annual growth rate since 1991. Proliferations of in-use tricycles in the market were found to be significant source of noise, particulates and pollutants (i.e., HC, CO, NOx) that creates adverse impacts on humans and the environment. In-use tricycles aggravate the problem of air pollution due to poor vehicle maintenance, extended service life, use of adulterated fuel and lubricants, excess use of lubricants, and overloading of passengers. Today, stringent standards are set in the Philippine Clean Air Act (CAA, 1999) for regulation of the idle CO at 4.5% (for MC/TC registered before January 2003 and 6.0% after January 2003) and HC at 7,800ppm (for registered MC/TC in urban areas and 10,000ppm for rural areas), however the implementation of these standard remains a challenge in the tricycle sector.Drive cycle is a vehicle speed-time curve that forms the basis of trace measurements of vehicle characteristics such as fuel consumption and exhaust emissions that are useful in the development of standards necessary for both vehicle performance and emission limits. The paper thereof intends to establish the on-road drive cycle pattern and conduct emission measurement to quantify tricycle emission contribution in urban residential environments. The improvised use of portable cyclo-computer, the CC-MT300TM CatEye Mity 3 for bicycles, was adapted to measure on-road speed trends, while a Horiba MEXA-554J, an automotive three-gas analyzer was used to measure CO and HC emissions at 1-second intervals during actual driving condition. The study methodology includes drive cycle testing and emission testing. The data collection and analysis involve: 9A) development of data collection and testing procedures, (b)development of drive cycle, and (c) development of emission models for the various experimental treatments of nine two-stroke tricycles and one four-stroke tricycle. The engine operation parameters (i.e., cylinder size, displacement, and motor brand/model) and experimental treatment parameters such as load variation and fuel-oil ratio (i.e., engine oil) were adopted. Results of the study revealed that for tricycles two-stroke type of engine, the idle speed condition the CO concentration average at 3.73% (max. at 7.93%) while its HC concentration average at 6,048ppm (max. at 13,040ppm). In contrast, at running speed condition the CO emission average at 3.72% (max. at 9.74%) while its HC emission average at 6, 089ppm (max. at 13,370ppm). However, for four-stroke type tricycle the CO concentration average at 2.28% (max. at 4.25%) while its HC concentration average at 307ppm (max. at 620ppm) and ta running speed condition the CO emission average at 2.29% (max. at 6.16%) while its HC emission average at 339ppm (max. at 1,104ppm). These indicate that four-stroke tricycles emit less emission compared to two-stroke type. The analyses of the CO regression models revealed that emissions are significantly affected by fuel-oil ration and loading, and that there is a significant correlation between CO and HC concentration. Finally, the study was able to develop the drive cycle for tricycle with maximum speed of 43.0kph, maximum acceleration of 6.97m/s2 (minimum acceleration of 6.44 m/s2), and average speed of 19.94kph.